Comparative study of the weft-knitted strain sensors - TUNÇAY ATALAY, ASLI (SAGE PUBLICATIONS INC, 2017)
In this study, weft-knitted strain-sensing structures are described, along with the materials and manufacturing techniques required to produce the fabrics on a computerised flat-bed knitting machine. Knitted sensing fabrics with conductive yarns, i. e. silver-plated nylon yarn and polyester-blended stainless steel yarn have been created with different design possibilities. A laboratory test set-up was built to characterise the knitted sensors and the resulting equivalent resistance under the different level of strains. The most successful samples have been realised through a series of single conductive courses within the interlock base fabric structure using silver-plated nylon in terms of responsivity, repeatability and lower electrical signal drift. Deficiencies associated with strain-sensing structures realised through the intermeshing of conductive yarns have also been addressed.
Keywords: Strain sensor; textile-based sensors; conductive yarn; weft-knitted sensor; electronic flat-bed knitting machine; DESIGN; PARAMETERS